A miR-372/let-7 Axis Regulates Human Germ Versus Somatic Cell Fates. (17th May 2016) - Tran, Nam D.; Kissner, Michael; Subramanyam, Deepa; Parchem, Ronald J.; Laird, Diana J.; Blelloch, Robert H.
Abstract: The embryonic stem cell cycle (ESCC) and let-7 families of miRNAs function antagonistically in the switch between mouse embryonic stem cell self-renewal and somatic differentiation. Here, we report that the human ESCC miRNA miR-372 and let-7 act antagonistically in germline differentiation from human embryonic stem cells (hESCs) and human induced pluripotent stem cells (iPSCs). hESC and iPSC-derived primordial germ cell-like cells (PGCLCs) expressed high levels of miR-372 and conversely, somatic cells expressed high levels of let-7. Manipulation of miRNA levels by introduction of miRNA mimics or knockdown with miRNA sponges demonstrated that miR-372 promotes whereas let-7 antagonizes PGCLC differentiation. Knockdown of the individual miR-372 targets SMARCC1, MECP2, CDKN1, RBL2, RHOC, and TGFBR2 increased PGCLC production, whereas knockdown of the let-7 targets CMYC and NMYC suppressed PGCLC differentiation. These findings uncover a miR-372/let-7 axis regulating human primordial germ cell (PGC) specification. Abstract : Let-7 and miR-294 antagonistically regulate somatic versus germline fates through their influence on multiple cellular pathways.